DISIPLIN POSITIF: PENGUATAN SUMBER DAYA MANUSIA SMA NEGERI 14 AMBON - Mananggel, Marlin Blandy (Universitas Pattimura, 2025)
Challenges in maintaining discipline often affect the quality of interaction between teachers and students. Therefore, the positive discipline approach emerged as a strategy that focused on reinforcing good behavior and creating an inclusive learning environment. This community service activity aims to provide positive discipline training SMA Negeri 14 Ambon teachers an effort to strengthen teacher' soft skills, namely discipline, communication, leadership, patience, critical thinking and problem solving. This activity was conduct in four stages; preparation, implementation, evaluation, and reflection. The evaluation instrument used was a test, to measure the extent of teachers' understanding of the training materials delivered. The results of the pre-test and post-test analysis showed an average N-gain of 0.91 and was in the high category. This shows an increase in the basic abilities of the participants related to the application of positive discipline. Through this activity, participants gained insight into the importance of positive discipline in creating an inclusive learning environment, so that with the skills they have, participants can become pioneers in implementing positive discipline